CHARACTERISTICS AND DISTRIBUTION OF SPECIES OF THE ORDER CORACIIFORMES IN UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The article presents the results of the collected material concerning the occurrence and distribution of birds of the order Coraciiformes in Uzbekistan. Based on a comparative study of specimens of species belonging to this order and contained in ornithological collections, changes in their distribution at present were identified and analyzed. Based on data on species distribution, the most favorable habitats for their existence in Uzbekistan are described.